2016
DOI: 10.1104/pp.16.01463
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Metabolic Role of Mitochondria during Developmental Leaf Senescence

Abstract: The functions of mitochondria during leaf senescence, a type of programmed cell death aimed at the massive retrieval of nutrients from the senescing organ to the rest of the plant, remain elusive. Here, combining experimental and analytical approaches, we showed that mitochondrial integrity in Arabidopsis (Arabidopsis thaliana) is conserved until the latest stages of leaf senescence, while their number drops by 30%. Adenylate phosphorylation state assays and mitochondrial respiratory measurements indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
92
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 98 publications
(155 reference statements)
12
92
1
Order By: Relevance
“…Metabolic changes during leaf senescence have been mainly investigated in Arabidopsis [11,13,32]. They showed many similar features to what we found here in barley, such as the accumulation of minor CHO and the decrease in most of the amino acids like glutamine, glutamate, aspartate, serine, glycine and arginine.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Metabolic changes during leaf senescence have been mainly investigated in Arabidopsis [11,13,32]. They showed many similar features to what we found here in barley, such as the accumulation of minor CHO and the decrease in most of the amino acids like glutamine, glutamate, aspartate, serine, glycine and arginine.…”
Section: Discussionsupporting
confidence: 50%
“…While pipecolate and α-aminoadipate decreased in primary leaves with senescence, they sharply accumulated in flag leaves with ageing, suggesting that lysine was used for mitochondria respiration in seedlings but not so much in the flag leaves. The anapleurotic respiration of amino acids has been mainly observed in Arabidopsis in response to dark stress [32,34,37] and Chrobok et al [32] showed that the whole metabolic pathway of lysine degradation was up-regulated in Arabidopsis individual darken leaves. It could then be possible that the differences of light environment between primary and flag leaves are the reason of these discrepancies and that lysine level could be related to both glutamate content and TCA replenishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During leaf senescence in individually darkened leaves in Arabidopsis, the number of mitochondria decreases (Keech et al, 2007), probably by autophagy . The remaining mitochondria retain their motility and respiration activity until the last step of leaf senescence (Keech et al, 2007;Keech, 2011;Ruberti et al, 2014;Chrobok et al, 2016). These mitochondria are thought to provide energy and metabolites for degrading the cell components and relocating them to other younger parts of the plant (Keech et al, 2007;Keech, 2011;Ruberti et al, 2014;Chrobok et al, 2016).…”
Section: Other Factors Structures and Phenomena Related To Mitochonmentioning
confidence: 99%
“…Other organelles, such as mitochondria and peroxisomes, remain active much longer and provide energy for the cell as well as take over a number of metabolic tasks during this process (Keech et al, 2007;Chrobok et al, 2016). While yeast and animals possess mitochondrial PPases (Lundin et al, 1991;Curbo et al, 2006), so far no mitochondrial PPase has been identified in plants.…”
mentioning
confidence: 99%